The Role of Influencers, Brand Image, Ease of Use, and Consumer Trust in Electric Vehicle Purchase Decisions - Fariq Zabran Adha; Suhardi (Al-Qalam Institue, 2025)
The adoption of electric vehicles (EVs) is a critical issue in the global effort to reduce carbon emissions and transition to sustainable transportation systems. In Indonesia, despite government incentives and environmental awareness, the uptake of EVs remains slow. This study aims to examine the influence of influencer marketing, brand image, and ease of use on electric vehicle purchasing decisions, with consumer trust as a mediating variable. A quantitative approach was used, with a survey conducted among 113 potential EV consumers in Indonesia. Data analysis was performed using Structural Equation Modeling – Partial Least Squares (SEM-PLS). The results show that brand image and ease of use significantly enhance consumer trust, while influencer marketing directly influences purchasing decisions without mediation through trust. Consumer trust plays a key role in purchasing decisions but does not fully mediate all relationships. The findings highlight that while influencer marketing raises awareness, building trust for high-tech products like EVs requires deeper validation. This study contributes to consumer behavior and digital marketing literature, offering practical insights for enhancing EV adoption strategies in Indonesia